INTERNATIONAL COOPERATION IN THE CONTEXT OF THE INTEGRATION OF EDUCATION INTO THE EUROPEAN EDUCATIONAL AREA FOR THE DEVELOPMENT OF UKRAINE (Innovative professional education, 2024)
The European choice in the direction of professional  education reform as the main strategy of the state education policy is one of the important problems. Therefore, the issue of international cooperation in the process of integrating education into the European educational space is extremely relevant.
Keywords: international cooperation, integration of education, European educational space, environmental problems, reconstruction of Ukraine